Short-term survival of acute respiratory distress syndrome patients due to influenza virus infection alone: a cohort study. Issue 4 (10th November 2020) - Gacouin, Arnaud; Lesouhaitier, Mathieu; Reizine, Florian; Pronier, Charlotte; Grégoire, Murielle; Painvin, Benoit; Maamar, Adel; Thibault, Vincent; Le Tulzo, Yves; Tadié, Jean Marc
Background: Influenza virus (IV)-related pathophysiology suggests that the prognosis of acute respiratory distress syndrome (ARDS) due to IV could be different from the prognosis of ARDS due to other causes. However, the impact of IV infection alone on the prognosis of ARDS patients compared to that of patients with other causes of ARDS has been poorly assessed. Methods: We compared the 28-day survival from the diagnosis of ARDS with an arterial oxygen tension/inspiratory oxygen fraction ratio ≤150 mmHg between patients with and without IV infection alone. Data were collected prospectively and analysed retrospectively. We first performed survival analysis on the whole population; second, patients with IV infection alone were compared with matched pairs using propensity score matching. Results: The cohort admitted from October 2009 to March 2020 consisted of 572 patients, including 73 patients (13%) with IV alone. On the first 3 days of mechanical ventilation, nonpulmonary Sequential Organ Failure Assessment scores were significantly lower in patients with IV infection than in the other patients. After the adjusted analysis, IV infection alone remained independently associated with lower mortality at day 28 (hazard ratio 0.51, 95% CI 0.26–0.99, p=0.047). Mortality at day 28 was significantly lower in patients with IV infection alone than in other patients when propensity score matching was used (20% versus 38%, p=0.02). Conclusions: Our results suggest that patients with ARDS following IV infection alone have a significantly better prognosis at day 28 and less severe nonpulmonary organ dysfunction than do those with ARDS from causes other than IV infection alone. Influenza virus infection alone is associated with a better short-term prognosis than are other causes of ARDS https://bit.ly/31W2Mh2